The literatures of the French Pacific : reconfiguring hybridity - Ramsay, Raylene L. (Contemporary French and francophone cultures, 2014)
This title argues that the particularity of the forms of mixing in the literatures of the French Pacific country of New Caledonia contest and complexify the characterisations of hybrid cultural exchange.